1971
DOI: 10.1172/jci106681
|View full text |Cite
|
Sign up to set email alerts
|

The effects of intra-aortic counterpulsation on cardiac performance and metabolism in shock associated with acute myocardial infarction

Abstract: A B S T R A C T The effect of intra-aortic counterpulsation (IACP, 22-94 hr) on hemodynamics and cardiac energetics was evaluated in 10 patients in shock after acute myocardial infarction. The data clearly indicate that IACP improves myocardial oxygenation, enhances peripheral perfusion, and probably improves myocardial contractility in the severely diseased heart.Before treatment, decreases in cardiac index (mean value, 1.22 liter/min per m'), systolic ejection rate (67 ml/sec), and time-tension index per min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0
2

Year Published

1973
1973
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(49 citation statements)
references
References 52 publications
1
45
0
2
Order By: Relevance
“…In all patients, acute myocardial infarction was documented by a typical history, diagnostic electrocardiographic changes, and serum enzyme studies. Five patients had ventricular septal defect (VSD) [1][2][3][4][5][6][7][8][9] days after acute infarction. In two cases the infarction was anterior and in three inferior.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all patients, acute myocardial infarction was documented by a typical history, diagnostic electrocardiographic changes, and serum enzyme studies. Five patients had ventricular septal defect (VSD) [1][2][3][4][5][6][7][8][9] days after acute infarction. In two cases the infarction was anterior and in three inferior.…”
Section: Methodsmentioning
confidence: 99%
“…4 In contrast, counterpulsation can decrease ischemia by raising coronary perfusion pressure and will reduce afterload. [5][6][7][8][9][10][11][12] This report summarizes our experience in attempting to stabilize critically ill patients with these mechanical complications utilizing the intraaortic balloon pump (IABP).…”
mentioning
confidence: 99%
“…The beneficial effects of intra-aortic balloon pumping in relieving symptoms in patients with angina has been postulated to be due to an increase in coronary blood flow (due to diastolic pressure augmentation) and also due to decrease in myocardial oxygen demand (due to decreases in afterload and preload) (Gewirtz et al, 1982;Kerber et al, 1976;Sasayoma et al., 1982), and in fact, an increase in coronary blood flow has only been found in patients with cardiogenic shock (Mueller et al, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…24 First, IABP augments diastolic arterial pressure, which is an important determinant of the coronary driving pressure. We have previously demonstrated that IABP increases peak coronary blood flow velocity in patients after coronary angioplasty for anterior AMI.…”
Section: Proposed Mechanismmentioning
confidence: 99%